2015
DOI: 10.1007/s10103-015-1752-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy on bone repair: is there any effect outside the irradiated field?

Abstract: The biological effects of local therapy with laser on bone repair have been well demonstrated; however, this possible effect on bone repair outside the irradiated field has not been evaluated. The aim of this study was to investigate the effect of low-level laser therapy (LLLT) (λ = 830 nm) on repair of surgical bone defects outside the irradiated field, in rats. Sixty Wistar rats were submitted to osteotomy on the left femur and randomly separated into four groups (n = 15): group I, control, bone defect only;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 21 publications
1
25
0
10
Order By: Relevance
“…A recent experimental study showed that LLLT had a positive local biostimulative effect in the early stages of bone healing [20]. In concordance, our results showed better bone healing after LLLT compared to the control group, with statistically significant difference (p < 0.000).…”
Section: Discussionsupporting
confidence: 90%
“…A recent experimental study showed that LLLT had a positive local biostimulative effect in the early stages of bone healing [20]. In concordance, our results showed better bone healing after LLLT compared to the control group, with statistically significant difference (p < 0.000).…”
Section: Discussionsupporting
confidence: 90%
“…It is possible to find in literature a wide range of fluencies and energy of laser irradiation used by different authors on bone healing and fractures [9,23,24,40]. In a recent study, Batista et al, [46] used 830 nm laser irradiation, at 6 J, and presented a positive local biostimulative effect in the early stage of bone healing. Moreover, in an in vivo study comparing the effects of the 830 nm laser, at the energy of 1.7 and at 3.4 J, showed that the higher energy was more efficient to produce newly formed bone [8].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Phototherapy has been widely used in research of different tissues, such as tendons, peripheral nerve, skin tissue, bones, and muscle. [11][12][13][14][15][16] In this context, low-level laser therapy (LLLT), and light emitting diode therapy (LEDT) are efficient on bioenergetics muscle activation, and these effects may influence performance during physical activities. Therefore, researchers started to investigate LLLT and LEDT as a way to improve muscle performance as LLLT and LEDT induce photochemical effects on cells by light absorption at photoreceptors;phenomenon described as photobiomodulation.…”
Section: Introductionmentioning
confidence: 99%